Electron temperature diagnostics of aluminium plasma in a z-pinch experiment at the ＂QiangGuang-1＂ facility - 李沫 吴坚 王亮平 吴刚 韩娟娟 郭宁 邱孟通 (Chinese physics B, 2012)
Two curved crystal spectrometers are set up on the ＂QiangGuang-1＂ generator to measure the z-pinch plasma spectra emitted from planar aluminum wire array loads. Kodak Biomax-MS film and an IRD AXUVHS5# array are employed to record time-integrated and time-resolved free-bound radiation, respectively. The photon energy recorded by each detector is ascertained by using the L-shell lines of molybdenum plasma. Based on the exponential relation between the continuum power and photon energies, the aluminum plasma electron temperatures are measured. For the time-integrated diagnosis, several ＂bright spots＂ indicate electron temperatures between （450 eV- 520 eV） ± 35%. And for the time-resolved ones, the result shows that the electron temperature reaches about 800 eV±30% at peak power. The system satisfies the demand of z-pinch plasma electron temperature diagnosis on a - 1 MA facility.